Primary pulmonary artery sarcoma in the pediatric patient: Review of literature and a case report - Kim, Yong Yean (Radiol Case Rep, 2020)
Primary pulmonary artery sarcoma (PAS) is extremely rare in children. Nevertheless, distinguishing primary PAS from pulmonary embolism is critical to a child's survival. Primary PAS is commonly misdiagnosed as a pulmonary embolism due to similar presenting symptoms and radiographic findings. However, compared to adults, pulmonary embolism is rare in children, especially in patients who do not have predisposing factors or hypercoagulable state. We present a child with primary PAS which mimicked pulmonary embolism on presentation but eventually was resected and is doing well 5 years after resection. In the absence of predisposing factors or hypercoagulable state, solid tumors such as primary PAS should be considered when assessing a pediatric patient with presumed pulmonary embolism.